GAMBARAN RIWAYAT MEROKOK, KONSUMSI ALKOHOL, DAN HIPERTENSI KELUARGA PADA PENDERITA HIPERTENSI DI WILAYAH KERJA PUSKESMAS MANGGIS I KABUPATEN KARANGASEM BALI 2013 - Windhu Saputra; Luh Seriani; Ketut Sudinda (DiscoverSys Inc., 2015)
Hypertension is a chronic disease which diagnosed by increased blood pressure above normal value. From Riskesas study on 2010, the hypertension cases was affect around 8,4 million people. On manggis district itself, the prevalence of hypertension cases on their area of duty was increased from 150 cases to 320 cases in 2013. The most determining risk factor of hypertension morbidity were lifestyle and family history. From the study of 50 people which selected by sampling in Manggis district, we found that around 70% of sample population have a family history of hypertension. From the history of tobacco use, roughly 58% of sample population didn’t take any tobacco at all. Also most of the people never drink any kind of alcohol which counted 52%.